EFEKTIVITAS KULIT PISANG KEPOK (Musa acuminat a balbisiana Colla) DALAM MENGUBAH KADAR LOGAM TIMBAL (Pb) - Nugroho Dwi Kuncoro (JURNAL TECHLINK, 2019)
Waste water containing lead (Pb) is very dangerous for the survival of humans and other living things. The researchers' goal in this case is to reduce the metal content of lead (Pb) contained in the water. The method used is the immersion system using banana peels kapok. The results obtained banana skin can absorb Pb content of waste water with the level of effectiveness of 75.64% at 5 grams a day to three, the effectiveness of 82.28% on addition of 10 grams of a banana skin for 3 days and the effectiveness of Pb 85.66% decline in the addition of 15 grams of a banana skin for 3 days. It is the addition of a banana skin kapok provide significant influence on the effectiveness of a decrease in metal content of lead (Pb) in water.